The pedagogical support system for students working at school - O. V. Tumasheva; M. B. Shashkina (Russian State Vocational Pedagogical University, 2024)
Introduction. The acute shortage of young teachers currently observed in Russia is of particular interest to students who have already started working in the education field during their studies. The search for ways to support and prevent potential difficulties for such students is the subject of discussion. Aim. The aim of the study is to explore potential strategies to assist students from pedagogical universities who are working in schools while mastering the basic professional educational programme. Methodology and research methods were based on systemic, activity-based, and personality-oriented approaches. Theoretical (analysis and author's interpretation of psychological and pedagogical literature on the problem of accompanying higher education students, systematisation, and generalisation of scientific research results) and empirical (questionnaires, interviews, analysis and interpretation of results, pedagogical modelling) methods were used. Results and scientific novelty. The study presents a proven pedagogical system that considers the full cycle of support aimed at identifying the challenges faced by working students, determining the main directions of targeted support, implementing it, and fostering the development of students in educational and professional activities. The content and format of the subjects' activities at each stage of support are described: preparation, correction, enrichment, reflection. The dyads "student-teacher" and "young teacher-teacher-mentor" are combined to address the shared goal of offering comprehensive support. Practical significance. The developed model of support for students at a pedagogical university who are working at schools can be implemented in the training of future teachers at the university and in the educational institutions where the students are employed.